Association between illness perception and clinical control, quality of life, physical activity, and psychosocial status in subjects with moderate to severe asthma: a cluster analysis - Silva, Simone T Camargo; Freitas, Patrícia Duarte; Lunardi, Adriana Claudia; Xavier, Rafaella Fagundes; Barbosa, Renata Cleia C; Stelmach, Rafael; Carvalho, Celso R F (The Journal of asthma, 2023)
Illness perception (IP) is a psychosocial factor involved in several chronic diseases and is associated with relevant clinical outcomes. However, the relationship between IP and health-related quality of life (HRQoL), psychosocial status, and physical activity in daily life (PADL) in subjects with asthma is poorly understood. To identify groups of subjects with asthma based on their IPs and to assess their association with clinical control, HRQoL, psychosocial disturbances, and PADL. This cross-sectional study included 149 subjects with moderate to severe asthma. IP, anthropometric data, Asthma Control Questionnaire-7, Asthma Quality of Life Questionnaire, Hospital Anxiety and Depression Scale, PADL (accelerometry), and general self-efficacy (GSE) were assessed. Cluster analysis was performed to identify clusters with similar profiles and investigate their characteristics and differences. Pearson's correlation coefficient was used to test the associations between IP and other variables. Statistical analyses identified two clusters of subjects with asthma based on IP. Cluster 1 presented worse IP in seven out of eight domains than Cluster 2. Cluster 1 had more negative consequences of the disease, worse understanding, and a high emotional representation of the disease than Cluster 2. Cluster 1 also had a greater extent of asthma symptoms, poor clinical control, worse HRQoL, and more symptoms of anxiety and depression. No difference between clusters was found for PADL or self-efficacy. Subjects with asthma who have worse IP have more negative symptoms, worse clinical control, HRQoL, and symptoms of anxiety and depression.